2020
DOI: 10.1007/s10456-020-09755-5
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis, hereditary hemorrhagic telangiectasia and COVID-19

Abstract: Hereditary hemorrhagic telangiectasia (HHT) is a rare autosomal-dominant disease characterized by pathologic angiogenesis that provokes vascular overgrowth. The evidence about the influence of Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) in patients with rare diseases is scarce. We aimed to know the prevalence of coronavirus disease 2019 (COVID-19) in HHT patients. The HHT pathogenic angiogenesis and endothelial injury in COVID-19 are discussed using data from RiHHTa (Computerized Registry of Heredita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
7
2
Order By: Relevance
“…None of the COVID-19 patients identified in the present study suffered from these serious complications, which prevented us from addressing this issue. Even though a weaker severity of infection symptomatology has been hypothesized in HHT patients, in terms of hospitalization rate and need for ventilation [ 43 , 50 ], potentially attributing to reduced endothelial damage and/or impaired inflammatory cytokine profile, our result do not seem to support this scenario, as 2/296 interviewed patients were hospitalized for COVID-19 pneumonia across Italy, also requiring ventilatory support or intubation. In HHT, Riera-Mestre et al [ 50 ] have reported a low hospitalization prevalence for COVID-19 pneumonia (1/1177), and Marcos et al [ 43 ] have observed a mild degree of manifestations in all patients affected by COVID-19 (only 3/138 individuals required hospitalization, none of them needing ventilation or intensive care).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…None of the COVID-19 patients identified in the present study suffered from these serious complications, which prevented us from addressing this issue. Even though a weaker severity of infection symptomatology has been hypothesized in HHT patients, in terms of hospitalization rate and need for ventilation [ 43 , 50 ], potentially attributing to reduced endothelial damage and/or impaired inflammatory cytokine profile, our result do not seem to support this scenario, as 2/296 interviewed patients were hospitalized for COVID-19 pneumonia across Italy, also requiring ventilatory support or intubation. In HHT, Riera-Mestre et al [ 50 ] have reported a low hospitalization prevalence for COVID-19 pneumonia (1/1177), and Marcos et al [ 43 ] have observed a mild degree of manifestations in all patients affected by COVID-19 (only 3/138 individuals required hospitalization, none of them needing ventilation or intensive care).…”
Section: Discussioncontrasting
confidence: 75%
“…Even though a weaker severity of infection symptomatology has been hypothesized in HHT patients, in terms of hospitalization rate and need for ventilation [ 43 , 50 ], potentially attributing to reduced endothelial damage and/or impaired inflammatory cytokine profile, our result do not seem to support this scenario, as 2/296 interviewed patients were hospitalized for COVID-19 pneumonia across Italy, also requiring ventilatory support or intubation. In HHT, Riera-Mestre et al [ 50 ] have reported a low hospitalization prevalence for COVID-19 pneumonia (1/1177), and Marcos et al [ 43 ] have observed a mild degree of manifestations in all patients affected by COVID-19 (only 3/138 individuals required hospitalization, none of them needing ventilation or intensive care). Discrepancy can be accounted for by the different approach of our study, which aimed to fully characterize the clinical spectrum of HHT patients with COVID-19 and to weigh the results according to the geographical distribution of epidemic foci, in a nation-wide manner, whereas focusing only on COVID-19-pneumonia-related hospital admission [ 50 ], or investigating a single cohort attending a reference HHT ENT consult [ 43 ], without normalizing for epidemiological profile, might result in an incomplete description of COVID-19 clinical array in a rare disease as HHT.…”
Section: Discussioncontrasting
confidence: 75%
“…We will try to discuss the possible factors explaining the COVID-19 less severe symptoms among HHT patients. As a previous reference, Riera et al [ 22 ] reported only one case of a HHT2 COVID-19-positive patient admitted to hospital, in Spain, after the first wave of 2020. The patient was a woman of 74 years, and was hospitalized due to a COVID-19-derived pneumonia.…”
Section: Discussionmentioning
confidence: 98%
“…Her clinical course did not involve mechanical ventilation, and she was successfully discharged after two weeks. In this letter [ 22 ], the authors refer to this case as the only HHT case admitted in hospital among the RiHHTa (Computerized Spanish Registry of Hereditary Hemorrhagic Telangiectasia). The authors hypothesize that the condition of HHT leads to a damaged endothelium with inflammation and an abnormal angiogenesis which would impair the SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, it is mandatory to develop alternative methods to provide assistance to patients, in particular those with peculiar needs [ 8 , 9 , 10 , 11 , 12 ]. In the specific field of rare diseases, the development of telemedicine and remote consultation is fundamental, as many of these patients have been experiencing a feeling of fear and abandon during the COVID-19 pandemic, with many cases of poor compliance to therapy and discontinuation of important treatments [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%